(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This article examines the key characteristics of well-designed language assessment items within the context of Uzbekistan’s educational system. It analyzes current practices, challenges, and opportunities for improvement in test item development based on international standards while addressing the unique linguistic and cultural considerations relevant to Uzbek language learners.